2022
DOI: 10.1128/spectrum.00139-22
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Structural Characterization of Diverse NfsB Chloramphenicol Reductase Enzymes from Human Pathogens

Abstract: The question of how new enzyme activities evolve is of great biological interest and, in the context of antibiotic resistance, of great medical importance. Here, we have tested the hypothesis that new antibiotic resistance mechanisms may evolve from promiscuous housekeeping enzymes that have antibiotic modification side activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Strongly depending on the affinity for the substrates, different product distributions are observed for NsfB. Indeed, NfsB is known to contribute to chloramphenicol resistance in Gram-negative bacteria by reduction of chloramphenicol to its corresponding inactive aminochloramphenicol, [54,55] but likewise induces susceptibility of Gram-negative bacteria towards nitrometronidazol by conversion into its hydroxylamine [55] involved in radical processes damaging the bacterial DNA. In our current mechanistic understanding of the overall reaction, the initial reduction of psGSLPEG(NO2)-N3 to the corresponding nitroso compound 22 (only detected in traces, Scheme 4) and subsequently to the hydroxylamine 21 as major reduction product is fast.…”
Section: Resultsmentioning
confidence: 99%
“…Strongly depending on the affinity for the substrates, different product distributions are observed for NsfB. Indeed, NfsB is known to contribute to chloramphenicol resistance in Gram-negative bacteria by reduction of chloramphenicol to its corresponding inactive aminochloramphenicol, [54,55] but likewise induces susceptibility of Gram-negative bacteria towards nitrometronidazol by conversion into its hydroxylamine [55] involved in radical processes damaging the bacterial DNA. In our current mechanistic understanding of the overall reaction, the initial reduction of psGSLPEG(NO2)-N3 to the corresponding nitroso compound 22 (only detected in traces, Scheme 4) and subsequently to the hydroxylamine 21 as major reduction product is fast.…”
Section: Resultsmentioning
confidence: 99%
“…Resistance may emerge directly from elements with other metabolic functions or indicate a shared common ancestor. The recent finding that soil bacteria are capable of subsisting on antibiotics as the sole carbon source further supports a close association between antibiotic resistance and bacterial metabolism. Given the astounding number of bacterial cells on the planet (>10 30 ), the variety of metabolic enzymes that can serve as resistance elements, and the rapidity of bacterial cell growth, we believe that environmental bacteria capable of metabolizing aminoglycosides may also be widespread. Analyzing these bacteria could reveal aminoglycoside-degrading enzymes.…”
Section: Introductionmentioning
confidence: 84%
“…and Haemophilus influenzae , has been proposed in multiple reports in the early stages (Smith et al, 2007). However, only Mullowney et al (2022) identified the nitroreductase NfsB from the strain H. influenzae , which confers resistance to CHL by reducing the nitro group to the corresponding amine group.…”
Section: Introductionmentioning
confidence: 99%